Analisis SWOT terhadap Risiko dan Strategi Penyaluran Pembiayaan Konsumen di Lembaga Keuangan Syariah: Studi pada Bank Mega Finance Syariah Purwokerto - Nafila, Isna; Mukaromah, Siti; Ramadhanti, Salsabilla; Shafrani, Yoiz Shofwa (Fakultas Teknik Universitas Maritim AMNI Semarang, 2025)
This study aims to analyze the risks and strategies in consumer financing distribution at Bank Mega Finance Syariah Purwokerto using a SWOT (Strengths, Weaknesses, Opportunities, Threats) approach. Islamic financial institutions play a significant role in supporting community economic activities through financing products based on sharia principles. However, in practice, these institutions also face various challenges such as late installment payments, unauthorized transfer of financed assets, and intense competition in the financial services market. This research employs a qualitative descriptive method through direct observation and in-depth interviews with internal company parties, particularly the collection department. The results indicate that the main strength of Bank Mega Finance Syariah Purwokerto lies in its diverse financing services, including cash loans, vehicle financing, and smartphone credit. Its weaknesses include the risk of payment arrears and potential losses caused by customers who pawn or sell financed items. The institution’s opportunities are in market expansion through digital-based leasing registration applications, while its threats involve high competition and strict consumer protection regulations. These findings provide strategic recommendations for strengthening risk management and improving the quality of sharia-compliant financing services in Purwokerto and its surrounding areas.